2021
DOI: 10.1108/fs-05-2021-0098
|View full text |Cite
|
Sign up to set email alerts
|

Health-care preventive measures, logistics challenges and corporate social responsibility during the COVID-19 pandemic: break the ice

Abstract: Purpose The study aims to analyze the role of coronavirus testing capacity to possibly reduce the case fatality ratio (CFR) in a large cross-section of countries. The study controlled health-care expenditures, logistics performance index (LPI), carbon damages, and corporate social responsibility (CSR) to understand the nature of causation between the CFR and stated factors. Design/methodology/approach The study used a cross-sectional regression apparatus for coefficient estimates and variance decomposition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There is no direct study available on the topic. In contrast, the latest study of Sasmoko et al (2021) found the W-shaped relationship between case fatality ratio and case-to-test ratio in the presence of corporate social responsibility and LPI. However, the direct N-shaped relationship is overlooked between the HLPI and coronavirus cases, which exerts a serious policy implication to reduce pandemic through the free flow of medical logistics supply in SSA economies.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…There is no direct study available on the topic. In contrast, the latest study of Sasmoko et al (2021) found the W-shaped relationship between case fatality ratio and case-to-test ratio in the presence of corporate social responsibility and LPI. However, the direct N-shaped relationship is overlooked between the HLPI and coronavirus cases, which exerts a serious policy implication to reduce pandemic through the free flow of medical logistics supply in SSA economies.…”
Section: Introductionmentioning
confidence: 76%
“…The increasing health-care compromises make community health more vulnerable than likely to be affected by contagious diseases, including the COVID-19 pandemic. The transformation from fossil fuels to renewable fuels in logistics operations would be helpful to improve the country’s health and wealth agenda (Anser et al , 2021a, 2021b; Sasmoko et al , 2021). The logistics supply was largely disrupted because of nationwide lockdown in many parts of the globalized world to contain coronavirus cases (Yu et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it reduces societal costs and expands access to preventive treatment. Preventative interventions in healthcare, such as the logistical supply of protective equipment and improved corporate social responsibility, may help minimize sensitive COVID-19 cases (Sasmoko et al 2021). Healthcare supply chain management contributes to pandemic containment by implementing sustainable business strategies (Sriyanto et al 2021).…”
Section: Theoretical Underpinningmentioning
confidence: 99%